Kartagener’s Syndrome: A Rare Case - Richa, -; Abrol, Pankaj; Sharma, Shashi; Madan, Sakshee (Journal of Nepal Paediatric Society, 2020)
Kartagener’s syndrome, an autosomal recessively inherited disorder, is a subgroup of primary ciliary dyskinesias. This genetic disorder manifests from early life which distinguishes it from acquired mucociliary disorders. Kartagener’s syndrome presents as a classical triad of situs inversus, sinusitis and bronchiectasis occurring majorly due to impaired ciliary motility. Here we report a case of a four year old female child who presented to us with repeated episodes of cough and intermittent breathlessness for the past three years. Clinical examination revealed bilateral coarse basal crepitations and apex beat on right fifth intercostal space in the midclavicular line. A thorough investigation revealed situs inversus, chronic sinusitis, and bilateral bronchiectasis. The patient underwent a high-speed video microscopy analysis which was suggestive of primary ciliary dyskinesia. Considering these findings, the patient was diagnosed as a case of Kartagener’s syndrome.